Physical fitness and academic performance among undergraduate students of a public university in Malaysia - Maghsoudi, Emad; Kandiah, Mirnalini; Lim, Wai Kong; Mohd Yusof, Barakatun Nisak; Appukutty, Mahenderan (Scholars Research Library, 2014)
Physical Fitness and Academic Performance among Undergraduate Students of a Public University in Malaysia: This study investigated the relationship between health-related components of physical fitness consisting of morphological fitness (body fat % or BF %; Body Mass Index or BMI; and waist circumference or WC), metabolic fitness (blood glucose, lipid profiles and haemoglobin) and aerobic capacity (VO2max) with academic performance. This cross-sectional study involved 324 volunteer undergraduates in their first year of study recruited by systematic random sampling from a public university in the city Shah Alam, Malaysia. Physical fitness was measured by anthropometric measurements using standard protocols and field fitness tests. Students‘ registration numbers linked the university database to import the Cumulative Grade Point Average. A weak, negative significant relationship was found between WC and academic performance (r = -0.120, p = 0.034). There was a weak negative significant relationship between VO2max and academic performance (r = -0.128, p = 0.029). There was a negative, medium significant relationship between LDL-cholesterol and academic performance (r = -0.505, p = 0.017). Running of Linear regression analysis (stepwise) showed that household income (Ɓ = 0.125, R2= 2.9%) and waist circumference (Ɓ = -0.005, R2 = 1.7%) contributed significantly towards academic performance (F = 7.29, p<0.05). Although waist circumference contributed significantly towards academic performance, it cannot be concluded that health component of physical fitness enhance academic performance since the association is so weak.